A Game Dimension Function - Önal, Süleyman; Soyarslan, Servet (Topology Proceedings, 2021)
We define a topological game dimension, ($gd$), such that $gd(X) = Ind(X)$ where $X$ is a hereditarily normal space and $Ind(X) ≤ gd(X)$ where $X$ is a normal space. We ask a question which is about whether $gd(X) = Ind(X)$ where $X$ is a normal space. By making some appropriate modifications in this game, the dimension functions $Ind$ and $ind$ can be characterized in the realm of normal spaces.